Terjebak dalam Pikiran Sendiri: Dampak Overthinking terhadap Depresi pada Remaja Broken Home - Agustian, Saefuddin Dicky; Azzahra, Berliana Rizka Surya; Tasaoktora, Aflihatul Ulya; M, Muslikah; Mahfud, Ashari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Adolescence is a critical phase in individual development, marked by the search for identity and the need for emotional support from the family. However, adolescents from broken homes often face complex psychological pressures due to the absence of stable parental figures and an inharmonious family environment. One of the common psychological impacts is the tendency to experience overthinking, which is a repetitive thinking process without constructive solutions. This article aims to examine the relationship between overthinking and depression in adolescents from broken homes through a literature review approach. The results of the analysis show that overthinking, especially in the form of brooding, is highly correlated with symptoms of depression, such as social withdrawal, decreased achievement, and self-harm behavior. Non-adaptive coping mechanisms, cognitive distortions, and low self-acceptance also worsen the mental condition of adolescents in this group. Mindfulness therapy and cognitive-behavioral approaches have proven effective as interventions, but require systemic support from the school, community, and family environments. This study emphasizes the importance of mental health literacy and preventive interventions to build psychological resilience in adolescents in dealing with dysfunctional family dynamics.